Community Participatory Action Research for the Elderly Housing Development in Namai Sub-district, Ladlumkaew District, Phathumthani Province - Muangnok, Preeyapa; Thomchoho, Watcharakorn; Maikami, Mattanaporn; Tansripraparsiri, Sekporn (Arts of Management Journal, 2025)
This article aimed to 1) examine the conditions and challenges of housing preparation for elderly people in Narmai Sub-district, 2) promote knowledge of housing preparation for seniors, and 3) establish a housing development group for aging residents in Narmai Sub-district. The research was conducted using Participatory Action Research. The tools for data collection included SWOT Analysis, SOAR Analysis, and interviews. The statistical data were analyzed using descriptive methods. The research findings were as follows: 1. The condition of problems and needs: The strength was the effectiveness of community leaders. The aged people were able to help themselves and had economic stability. The weakness was that the community lacked knowledge of housing preparation for aged people. The opportunity was that both the internal and external agencies were ready to offer support. The threat was the local development plan of the Sub-district Administrative Organization, which gave little support to the knowledge development of aged people’s quality of life. The aspiration was the requirement of the community to enhance their knowledge to provide a good quality of life for aged people and ensure housing safety. 2. Promoting learning: The researcher created learning media in the form of VDO and a handbook and organized training on safety housing preparation for elderly people. 3. Establish groups to promote housing development for the elderly, involving community leaders, the District Administrative Organization, the District Health Promotion Hospital, and Valaya Alongkorn Rajabhat University. With this data and knowledge, local administrative organizations can incorporate it into their development plans.